Identity perspectives regarding Israeli-Arab youth participating in voluntary national service in Israel - SEMAAN, Seline (Studia Universitatis Babes-Bolyai Studia Europaea, 2025)
This article examines the perspective of Israeli-Arab youth regarding their participation in Voluntary National Service (VNS) within the context of Israel's political landscape. VNS is an alternative to mandatory military service to foster social integration and civic responsibility. However, for Israeli-Arab youth, VNS often leads to significant identity conflict, shaped by Israel's characterization as a Jewish and democratic state and ongoing regional tensions. The article identifies various factors contributing to this identity conflict through a comprehensive literature review. The finding offers insights for policymakers seeking to foster a more inclusive environment for Israeli-Arab citizens.